At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
The function of the equation is f(x) = [tex]-\frac{1}{2}[/tex] [tex]-\frac{3}{2}[/tex] x
Step-by-step explanation:
The function form of the linear equation is f(x) = m x + b, where
- m is the slope of the line represents the graph of the function
- b is the y-intercept
∵ The equation is 3x + 7 = 2(3 - y)
→ Simplify the right side by multiplying the bracket by 2
∵ 3x + 7 = 2(3) - 2(y)
∴ 3x + 7 = 6 - 2y
→ Add 2y for both sides
∵ 2y + 3x + 7 = 6 - 2y + 2y
∴ 2y + 3x + 7 = 6
→ Subtract 7 from both sides
∵ 2y + 3x + 7 - 7 = 6 - 7
∴ 2y + 3x = -1
→ Subtract 3x from both sides
∵ 2y + 3x - 3x = -1 - 3x
∴ 2y = -1 - 3x
→ Divide each term by 2
∴ y = [tex]-\frac{1}{2}[/tex] - [tex]\frac{3}{2}[/tex] x
→ Replace y by f(x)
∴ f(x) = [tex]-\frac{1}{2}[/tex] [tex]-\frac{3}{2}[/tex] x
∴ The function of the equation is f(x) = [tex]-\frac{1}{2}[/tex] [tex]-\frac{3}{2}[/tex] x
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.